First Record of Ategmic Ovules in Orchidaceae Offers New Insights Into Mycoheterotrophic Plants - Alves, Mariana Ferreira; Pinheiro, Fabio; Niedzwiedzki, Marta Pinheiro; Mayer, Juliana Lischka Sampaio (Frontiers in Plant Science, 2019)
The number of integuments found in angiosperm ovules is variable. In orchids, most species show bitegmic ovules, except for some mycoheterotrophic species that show ovules with only one integument. Analysis of ovules and the development of the seed coat provide important information regarding functional aspects such as dispersal and seed germination. This study aimed to analyze the origin and development of the seed coat of the mycoheterotrophic orchid Pogoniopsis schenckii and to compare this development with that of other photosynthetic species of the family. Flowers and fruits at different stages of development were collected, and the usual methodology for performing anatomical studies, scanning microscopy, and transmission microscopy following established protocols. P. schenckii have ategmic ovules, while the other species are bitegmic. No evidence of integument formation at any stage of development was found through anatomical studies. The reduction of integuments found in the ovules could facilitate fertilization in this species. The seeds of P. schenckii, Vanilla planifolia, and V. palmarum have hard seed coats, while the other species have seed coats formed by the testa alone, making them thin and transparent. P. schenckii, in contrast to the other species analyzed, has a seed coat that originates from the nucellar epidermis, while in other species, the seed coat originates from the outer integument.